Well-being, spirituality and fear of COVID-19 in older adults during the first year of the pandemic - Ruiz Bartra, Diana Haydeé (2024)
The COVID-19 pandemic has had a profound global impact. Within this context, the well-being of one of the most vulnerable groups, older adults, deserves significant attention. Hence, this study aimed to analyzed the relationships between Fear of COVID-19, Spirituality, and Well-Being of a sample of 169 older adults from Lima during the first year of the pandemic and, if significant relationships were found, evaluate what the variables had most impact in the well-being of this group. Previously, differences in these variables were analyzed according to reported socio-demographic and health characteristics. In order to measure Well-being, the Flourishing, SPANE-P and SPANE-N scales were used (Diener et al., 2010), for Fear of COVID-19 the FCV-19S (Ahorsu et al., 2022) and for Spirituality the SBI-15R (Holland et al., 1998). The results showed significant relationships between Fear of COVID-19 and all measures of Wellbeing. Also, a direct and significant relationship was found between Spirituality and Positive Affectivity. Regarding the variables that most explain the Well-being of the sample, the regression models revealed that the report of a chronic disease and the Fear of COVID-19 were the variables that most explained the Flourishing (adjusted R2=.4, p<001). Fear of COVID-19 and Spirituality had a negative impact on positive affectivity (adjusted R2=.19, p<001). Finally, Fear of COVID-19 and diagnosis of COVID-19 were the explanatory variables of Negative Affectivity (adjusted R2=.33, p<.001).